2012
DOI: 10.1016/j.agee.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Residual effects of lime and sewage sludge inputs on soil fertility and tree and pasture production in a Pinus radiata D. Don silvopastoral system established in a very acidic soil

Abstract: In Galician (Spain) silvopastoral systems, nutrient availability to the pasture and trees can be limited by soil acidity. Liming and fertilisation with sewage sludge could enhance the productivity of silvopastoral systems (including understory and trees) by increasing Ca and reducing Al in the soil. This study evaluated changes in soil chemical properties, tree growth and understory production in test plots, both limed and unlimed, in a silvopastoral system located on an acidic forest soil under Pinus radiata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
2
15
0
1
Order By: Relevance
“…In 2005, the liming negatively affected the soil pH probably because the pasture production tended to improve when the soil was limed (Lime 400N) compared with the treatment without lime (No Lime 0N), increasing the extraction of cations from the soil and thus causing soil acidification. Similar results were previously observed in the same area in silvopastoral systems established with Pinus radiata D. Don in which some years after the last addition of lime to the soil the soil pH decreased, mainly due to the quickly growth of the plants favoured by liming and the climatic conditions (Mosquera-Losada et al, 2012;Ferreiro-Dominguez et al, 2014). The increase in pasture production associated with liming could be attributed to the increase in the exchangeable Ca, which tends to increase mineralisation of the soil organic matter, causing nutrient release (Wheeler, 1998) and, therefore, improving the physical and chemical soil properties (Slattery et al, 1995).…”
Section: Lime Effectsupporting
confidence: 90%
See 1 more Smart Citation
“…In 2005, the liming negatively affected the soil pH probably because the pasture production tended to improve when the soil was limed (Lime 400N) compared with the treatment without lime (No Lime 0N), increasing the extraction of cations from the soil and thus causing soil acidification. Similar results were previously observed in the same area in silvopastoral systems established with Pinus radiata D. Don in which some years after the last addition of lime to the soil the soil pH decreased, mainly due to the quickly growth of the plants favoured by liming and the climatic conditions (Mosquera-Losada et al, 2012;Ferreiro-Dominguez et al, 2014). The increase in pasture production associated with liming could be attributed to the increase in the exchangeable Ca, which tends to increase mineralisation of the soil organic matter, causing nutrient release (Wheeler, 1998) and, therefore, improving the physical and chemical soil properties (Slattery et al, 1995).…”
Section: Lime Effectsupporting
confidence: 90%
“…The total amount of sewage sludge produced in the EU is expected to be 13 million tons in 2020 (EU, 2008). Moreover, several studies have showed that the use of sewage sludge as fertiliser in the silvopastoral systems could enhance tree growth and pasture production (Mosquera-Losada et al, 2012;Ferreiro-Dominguez et al, 2011 while the botanical composition of the understory (Mosquera-Losada et al, 2009b) and the soil C storage are modified (Mosquera-Losada et al, 2015). However, using sewage sludge as fertiliser can represent a potential threat to the environment due to the possible addition to the soil of heavy metals and toxic organic compounds, the excess of labile organic matter and leachable N and P and the presence of pathogenic microorganisms (McBride, 2003;McLaren et al, 2004;De las Heras et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Another paper, which compared the use of sewage sludge in comparison with the control and the area fertilized with mineral fertilizers (by 500 kg to 8% N -24% P 2 O 5 -16% K 2 O per hectare) also confirmed the positive effect of sewage sludge on the height of seedlings (Rigueira-Rodríguez et al 2010). On the other hand, the use of sewage sludge in combination with lime has not been confirmed as a positively functioning agent in the height of the seedlings (Mosquera-Losada et al 2012). Alginite influence with positive results in height increment has only been evaluated one year after planting Tužinský et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Como discutido na seção anterior, o uso de lodo de esgoto consiste em uma estratégia para elevar o pH do solo, o que se reflete também na sua relação com a planta. Mosquera-Losada et al (2012), trabalhando com um solo de pH em torno de 4,0, verificaram efeito da aplicação de calcário no desenvolvimento das árvores, apenas na ausência de lodo de esgoto. Portanto, com a aplicação desse insumo orgânico, pode-se suprimir a prática da calagem mesmo em solo ácido, sem prejuízo ao desenvolvimento das plantas.…”
Section: Efeito Da Adubação Orgânica Sobre As Característi-cas Das Plunclassified